Development of Strategic Decision Making In Supporting National Maritime Defense - Bastari, Avando; Sutrisno; Prabowo, Ayip Rivai (International Journal of Intelligent Systems and Applications in Engineering, 2022)
State defense is essentially all efforts that are universal in nature and are carried out with an awareness of the rights and obligations of all citizens, belief in their strength to maintain the survival of the nation, state, just and prosperous. The marine defense strategy model is one part of the Archipelago State Archipelago Marine Defense Strategy, referring to the dynamics of development of the Strategic Environment and the capabilities of available national resources. In assessing the maritime defense strategy of the archipelago, it is determined by the influence and interrelationships between one aspect and another. As a complex system, an analysis is needed to get a score on the assessment of the maritime defense strategy of the archipelago, which consists of aspects of developing Navy strength, aspects of the Integrated Fleet Weapon System, and aspects of Potential Threats. Then it is compiled in a dynamic model that can represent a value in the assessment of the maritime defense of the archipelago country which is projected based on the time dimension up to the next 15 years. In this thesis, the researcher uses a System Dynamic model approach that is integrated with the Fuzzy Weighted method to obtain a weight assessment of the value of each variable and sub-variable. The results of the formulation and simulation of the model with a dynamic system approach in the assessment of the maritime defense strategy of the archipelago, obtained scores for each strategy scenario as follows: (1) Fleet In Being strategy with an index value of 5.72, (2) Blockade scenario of 5.72, (3) Decisive Battle scenario 5.73, (4) combination scenario between fleet in being and blockade 5.72, (5) combination scenario of the fleet in being and decisive battle 5.78, (6) scenario of the combination of blockade and decisive battle 5 .73 and the value of the defense of the marine dimension based on the current capability of the SSAT in the 15th year of 5.9 is included in the category of alert/quite safe.